2014
DOI: 10.5455/ijmsph.2013.230920132
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of aspiration cytology in suspected metastatic neck lymph nodes

Abstract: Background: Fine needle aspiration of neck nodes is quick, safe and convenient method for the diagnosis of various lesions. The procedure is well tolerated by the patients, has minimal complications and repeatable. Because of its minimally invasive characteristic, this technique is now being used routinely for quick and accurate diagnosis. Enlarged lymph nodes are one of the most frequently sampled tissues. The diagnostic accuracy of FNAC in neck node malignancy is high. Aims & Objective: To study efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
4
5
0
Order By: Relevance
“…21 However, Ojo et al found axillary nodes to be most common site of involvement followed by cervical lymph nodes. 22 In the present study most common metastatic lesion was Squamous cell carcinoma which was in concordance with results of S Prasad et al 14 and others. 1,17,23 It was followed by metastatic adenocarcinoma and metastatic duct carcinoma breast.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…21 However, Ojo et al found axillary nodes to be most common site of involvement followed by cervical lymph nodes. 22 In the present study most common metastatic lesion was Squamous cell carcinoma which was in concordance with results of S Prasad et al 14 and others. 1,17,23 It was followed by metastatic adenocarcinoma and metastatic duct carcinoma breast.…”
Section: Resultssupporting
confidence: 92%
“…In our study peak incidence of metastatic lesion was in the 4 th -6 th decade. Our findings correlated well with that of Ahmad et al and Sarda et al 11,12 Age range was almost comparable to Nesreen H. Hafez et al (4.5-82years) 13 but was less according to S Prasad et al (20 to 76 years) 14 ; but the most common age group affected were almost similar. In study done by Nesreen H. Hafez et al the mean age (46 years) 13 was slightly lower than our study.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Indian studies shown the higher result by whereas foreign authors have been reported lower results. [16][17][18] Ghartimagar et al, reported the incidence of metastasis to be more common in females than males with a male to female ratio of 1:1.25. 19 In most of studies, it has been observed that cervical lymph node involvement is most predominant in both benign and malignant disease process, possibly due to their proximity to anatomical passages of the body that is constantly exposed to environmental infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…FNAC has a significant role in neck lymph nodes, particularly those with metastasis. 3 FNAC confirms the presence of metastatic disease and gives a clue regarding its nature and origin of primary malignancy. It is very useful in detecting recurrence and new metastases.…”
Section: Introductionmentioning
confidence: 90%